Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)

Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)

Adopting a lay navigator training programme in primary care - Toal-Sullivan, Darene; Lemonde, Manon; Gauthier, Alain P.; Dahrouge, Simone (Health Education Journal, 2021)
Introduction: There is growing interest in the role and use of patient navigators within the health care system. Currently, qualifications and training expectations documented in the literature vary tremendously depending on context and patient population. This paper details the theoretical and pedagogical principles used to develop, implement and evaluate a training programme for lay patient navigators working in a primary care setting. Methods: The planning process involved (a) conducting an educational needs assessment, (b) identifying the theory underpinning the curriculum, (c) developing learning objectives and teaching strategies, (d) formulating evaluation methods, (e) implementing the programme and (f) refining the curriculum based on evaluation feedback and lessons learned. The training programme was first implemented in May 2017 and has evolved over the past 3 years based on our observations and feedback from the programme participants. Results: The training programme involves a total of 25 hours of online and face-to-face education sessions, and ongoing community mentorship from experienced navigators. All training components are rooted in theoretical principles and proven pedagogical approaches. The knowledge, skills and abilities acquired are also tied to core competencies of the role of lay patient navigator. Conclusion: The development of this lay navigator training programme was carefully designed with evidence-based competencies and practical realities to ensure rigour in preparing and supporting navigators’ work in primary care settings.

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society / Minorités linguistiques et société, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Understanding patient barriers and enablers to accessing community resources: a qualitative study to inform navigation service delivery - Saluja, Kiran; Mahbub, Adiba; Gauthier, Alain P.; Lemonde, Manon; Timony, Patrick; Durand, François; Dahrouge, Simone (BMC Primary Care, 2025)
Abstract Background Individuals face multifaceted barriers to accessing community resources, which can significantly impact their ability to obtain necessary support and services. This study examines barriers and enablers to access community resources among primary care patients and explores the interplay between individual- and system-level factors that influence access to resources. Methods In this qualitative study, we conducted 32 semi-structured interviews with primary care patients who participated in a social prescribing trial that compared two navigation services: ARC (patient-centered longitudinal support) vs. Ontario-211 (free 24-hour helpline service) in two regions, Ottawa and Sudbury, in the province of Ontario, Canada. We conducted thematic data analysis with a deductive/inductive hybrid approach, employing Levesque’s theoretical framework for access to health that examines the various system and individual level factors influencing access to healthcare services. Findings At the system level, various systemic barriers encompassing broader organisational, structural, and policy-related elements influenced patients' access to community resources (outreach, availability, location, costs and accommodations for patient needs and preferences). These factors directly interacted with various patient-level factors (awareness of needs, ability to seek support, to reach resources and to pay for those, their physical and mental health, motivation, and confidence to engage in care) to determine access. Conclusions Our findings highlight individual- and system-level barriers and enablers for accessing community resources among socially complex primary care patients with multiple unmet needs. As governments and organizations in Canada are increasingly investing in community-based services to address adverse social determinants of health (SDH), an upstream approach that reduces both systemic and individual-level barriers to access is warranted. Language significantly influences access to services, particularly for linguistic minorities (see page 5 and 7)

L’offre active de services de santé mentale en français en Ontario : données et enjeux - Cardinal, Linda; Normand, Martin; Gauthier, Alain P.; Laforest, Rachel; Huot, Suzanne; Prud’homme, Denis; Castonguay, Marcel; Eddie, Marie-Hélène; Savard, Jacinthe; Yaya, Sanni (Minorités linguistiques et société, 2018)
Au Canada, au gouvernement fédéral et dans plusieurs provinces, le principe d’offre active sert à guider la prestation des services publics en français. L’Ontario se démarque, car son approche est en partie volontaire. Il importe donc d’étudier comment les services en français sont intégrés à la gouvernance des services publics au sein de la province. Cet article puise dans les données gouvernementales existantes afin de brosser un tableau de l’offre active de services en français en santé mentale. Or, les auteurs montrent que ces données sont difficiles à obtenir et parcellaires. L’article sert à souligner des défis importants pour l’offre de services en français dans le domaine de la santé mentale en Ontario. Mots-clés : offre active, services en français, santé mentale, Ontario, données

Going the distance: a cross-sectional geospatial analysis quantifying province-wide inequities in travel-based access, and fragility of access to French-language primary care provided by family physicians in Ontario, Canada - Belanger, Christopher; Timony, Patrick E; Bélizaire, Arlynn; Desilets, Antoine; Fitzsimon, Jonathan Peter; Gauthier, Alain P; Godfrey, Leanda; Karunananthan, Sathya; Kehoe MacLeod, Krystal; Muray, Mwali-Nachishali; Peixoto, Cayden; Bjerre, Lise M (BMJ Open, 2026)
Objectives Language-concordant care, or healthcare in one’s preferred language, is important both for health equity and for improving health outcomes. Linguistic minorities, like Francophones in Ontario, Canada, are at risk of poorer clinical outcomes if they receive non-language-concordant primary care. However, common ratio-based access measures can provide misleading views of minorities’ actual access levels. This cross-sectional geospatial study demonstrates a new way to measure primary care access using average travel time to the nearest five English- and French-speaking family physicians. We also introduce the concept of primary care access fragility, where a region’s primary care access may depend on one or a few local family physicians. Our research question is: are there differences in travel burden and access fragility for census subdivisions (CSDs) across language (English/French), rurality (urban/rural) and region (north/south) in the province of Ontario, Canada? Design We conducted a cross-sectional geospatial analysis to estimate English-language and French-language primary care travel burdens and access fragility in Ontario, Canada. We used population and boundary data from Statistics Canada’s 2021 census, road-network data from OpenStreetMaps, and family physician practice locations and language abilities from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Setting: We conducted our analysis for Ontario, Canada’s 577 CSDs, which correspond roughly to municipalities and with populations ranging from 5 inhabitants in Rainy Lake 17B to a high of 2 794 356 in Toronto. Participants: Using public data from January 2026, we identified 15 762 family physicians practising in Ontario, of whom 11.0% reported speaking French. Patient data were obtained from the most recent 2021 census. Primary and secondary outcome measures: Our first primary outcome measures were CSD-level mean travel time to the nearest five English-speaking family physicians, and CSD-level mean travel time to the nearest five French-speaking family physicians, which we compared to explore regional inequities in travel burden. Our secondary outcome measures were based on a novel notion of the travel burden component of ‘primary care access fragility’. This metric indicates how dependent a region’s access is on a small number of local physicians and is defined as the difference between the CSD-level mean travel time to the nearest one physician and to the nearest five physicians. As the difference in travel times grows, so too does access fragility. Results Median differences in French-language and English-language travel burdens were strongly significant across rurality, regions and overall (median difference 13.4 min, p<0.001, IQR 4.9–29.3 min), as was primary care access fragility (median difference 5.2 min, p<0.001, IQR 0.8–18.4), with larger travel burdens and fragilities in northern and rural communities. Conclusions Compared with the general public, Ontario’s French-speakers face higher travel burdens to language-concordant family physicians and higher access fragility, especially in rural and northern regions. Our results are of interest to policymakers and health-system planners, and our methods are applicable to other populations and regions.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Disparities in COVID-19 infection rates across linguistic groups in long-term care homes in Ontario, Canada - Batista, Ricardo; Fitzgerald, Michael; Reaume, Michael; Kendall, Claire E.; Bjerre, Lise M.; Mahdavi, Roshanak; Imsirovic, Haris; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Helene; Hsu, Amy; Bouchard, Louise; et al. (BMC Public Health, 2026)
Background The COVID-19 pandemic has had a disproportionate impact on residents of long-term care facilities or nursing homes, characterized by significantly higher infection and mortality rates than in the general population. Previous research has highlighted significant disparities in COVID-19 outcomes, particularly among ethnic minorities. This study examines the association between belonging to a minority language community and COVID-19 infection rates in LTCFs in Ontario, Canada, at both the individual and facility levels. Methods We conducted a population-based retrospective cohort study of 85,367 LTC home residents in Ontario between January 15, 2019, and March 30, 2020, which we followed until March 31, 2021, using data from the Continuing Care Reporting System. We defined resident language (obtained from routine assessments in nursing homes) as English (Anglophone), French (Francophone), or other (Allophone), and we calculated a weighted average of languages spoken by residents in each LTC facility to determine the linguistic environment of the LTC facility. We calculated incidence rates of COVID-19 for each linguistic group, and we fitted multilevel logistic regression models to assess the main factors influencing the risk of COVID-19 infection, to account for individual-level and facility-level linguistic factors. Results The overall incidence of COVID-19 was 14.8%. The incidence of COVID-19 was higher among Allophones (23.6%) compared to Anglophones (13.1%) and Francophones (12.2%). Allophones in English homes (22.5%) showed significantly higher incidence rates compared to Anglophones (13.1%) and Francophones (11.0%) in these same homes. After adjusting for sociodemographic and clinical characteristics, the risk of COVID-19 remained significantly higher for Allophones compared to Anglophones (aOR 1.14, 95% CI 1.05–1.22), while residents living in language-discordant nursing homes had a non-significantly higher risk of COVID-19 (aOR 1.07, 95% CI 0.99–1.14). Conclusions Over the first two waves of the COVID-19 pandemic, the risk of COVID-19 infection in nursing homes was highest among residents whose primary language was a language other than English or French. The results of our study show that COVID-19 disproportionately affected populations living in minority linguistic communities. These findings may help informing public health interventions aimed at addressing the language barriers in long-term care in Ontario, and across Canada.